(untitled) (Economic Journal of Nepal, 2021)
COVID -19 pandemic has created the greatest economic crisis since the second world war. The main objective of this article is to analyse the impact of COVID-19 in the economy of South Korea. The article also looks at the various economic packages introduced by the government of South Korea to protect the people particularlylow-income families, informal-sector employees, part-timers, women, and the disabled. The article concludes that the country’s response tools and strategies in containing COVID-19 have been exemplary in the global community. The economic packages have been successful in creating jobs, boosting consumption and promoting investment. The modality of proper and effective cooperation and coordination among the levels of government and between the public and private sector played the vital role.